2008
DOI: 10.1136/gut.2007.142539
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and risk factor analysis for recurrence after curative endoscopic therapy in 349 patients with high-grade intraepithelial neoplasia and mucosal adenocarcinoma in Barrett's oesophagus

Abstract: This study showed that endoscopic therapy was highly effective and safe, with an excellent long-term survival rate. The risk factors identified may help stratify patients who are at risk for recurrence and those requiring more intensified follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
424
2
42

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(479 citation statements)
references
References 43 publications
11
424
2
42
Order By: Relevance
“…In this role, the adjunct use of a narrow light spectrum imaging technology, such as narrow band imaging, may aid in detecting mucosal irregularity ( 144 ). If such irregularity is detected, the next step in the management of that patient should be EMR or endoscopic submucosal dissection, both for therapeutic benefi t and to allow staging of the lesion ( 145,146 ). Although than previously believed ( 68,136,148 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In this role, the adjunct use of a narrow light spectrum imaging technology, such as narrow band imaging, may aid in detecting mucosal irregularity ( 144 ). If such irregularity is detected, the next step in the management of that patient should be EMR or endoscopic submucosal dissection, both for therapeutic benefi t and to allow staging of the lesion ( 145,146 ). Although than previously believed ( 68,136,148 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Cohort studies document that up to one-third of patients treated with EMR who achieve complete resection of the primary lesion will subsequently develop recurrent HGD or EAC ( 145 ). Whether these subsequent lesions represent undetected metachronous lesions or a fi eld eff ect in the susceptible patient is unclear.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…On the other hand, Pech et al ( 16 ) reported that the rate of metachronous recurrence was 21.5 % and Moss et al ( 40 ) reported a rate of 11 % in Western countries. Th is recurrence rate is higher than that in our study.…”
Section: Esophagusmentioning
confidence: 99%
“…In Western countries, some studies reporting results aft er ER for AC of the esophagus suggested a favorable prognosis, although the rates of local and metachronous recurrence were relatively high (4.2 ~ 21.5 % ) ( 15,16 ). Similarly, in Japan, some studies suggested a favorable prognosis aft er ER for SCC of the esophagus (0 ~ 2.3 % ) ( 17,18 ), although the rates of local and metachronous recurrence were also relatively high (16.4 ~ 20 % ) ( 19,20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cases with superficial submucosal invasion and high risk of complications with esophagectomy, endoscopic resection and ablation therapies can be considered a good therapeutic option, with encouraging results in highly selected patients (64). Ablation therapies after mucosal resection are highly recommended to eliminate the remainder BE, decreasing the risk of recurrence (65). In contrast, patients with deeper submucosal invasion have higher rates of lymphovascular involvement (63) and a multidisciplinary surgical oncology evaluation should be performed to assess the utility of endoscopic therapies, which are usually aimed to palliation (21).…”
Section: Management and Treatment Of Bementioning
confidence: 99%